THE IMPACT OF PARENTAL INVOLVEMENT IN TEACHING AND LEARNING ACTIVITIES ON EARLY CHILDHOOD SOCIAL- EMOTIONAL DEVELOPMENT - Sutari (International Journal of Teaching and Learning, 2025)
This literature research aims to evaluate the impact of parental involvement in teaching and learning activities on the social-emotional development of early childhood through systematic analysis of data available in academic literature. The methods used include a review of published empirical studies, journal articles, and educational theories with a focus on parental involvement and family dynamics, as well as their implications for children's social and emotional growth. The research results show that parental involvement substantially contributes to strengthening children's interpersonal skills, increasing emotional intelligence, and communicating a positive self-concept. Various factors such as the presence of parents during learning activities, consistency in emotional and educational support, and the parenting methods used, have been proven to be closely related to improving children's social skills and ability to regulate emotions. Furthermore, this research concludes that the supporting strategies implemented by educational institutions to increase parental involvement provide optimal benefits for children's development. Recommendations are aimed at educational practitioners to design collaborative frameworks that actively involve parents in the educational process, with the main aim of strengthening the social-emotional foundations of early childhood.